Prevalence and patterns of victimization and polyvictimization among female sex workers in Soweto, a South African township: a cross-sectional, respondent-driven sampling study. Issue 1 (1st January 2017) - Coetzee, J.; Gray, G. E.; Jewkes, R.
ABSTRACT: Background: Female sex workers (FSWs) are disproportionately affected by violence from multiple partner categories. This increases their vulnerability to HIV. Objectives: To describe patterns of violence and polyvictimization among female SWs in Soweto. Methods: A respondent-driven sampling (RDS) recruitment methodology was used to enrol 508 Soweto-based FSWs using a survey instrument. Raw and RDS adjusted data were descriptively analysed, Spearman's correlation and chi 2 test of association were used to show associations. Polyvictimization patterns are shown within a modified Venn diagram. Results: The median age of FSWs in Soweto was 31 years, and most had an incomplete education (74.2%). The prevalence of exposure to physical/sexual intimate partner violence (IPV) in the past year was 53.8%, 46.8% by clients, and 18.5% by police. Past year prevalence of sexual/physical violence by any perpetrator category was 70.8% and lifetime exposure was 76.0%. Childhood sexual violence was reported by 44.3%. Lifetime non-partner rape was 55.5% and all rape exposure was 62.4%. As a result of engaging in sex work in the past year, 65.2% women had been discriminated against. Client, police, IPV, and childhood trauma were all significantly associated with one another, with IPV being the most common co-occurrence. Polyvictimization was seen in almost two-thirds of FSWs, and increased with exposure to discrimination. Conclusion: In Soweto, FSWs are exposed to high rates of violence in multiple forms across their lifetime. Our findings show that violence continues unabated into adulthood at levels far higher than in the general population and overall at higher levels than previously recorded among SWs in South Africa. We argue that violence against FSWs is rooted in discrimination. The disparate burden of violence on FSWs requires urgent interventions to proactively address and reframe the normalisation of violence against all women.